Analisis SWOT sebagai Strategi Pengembangan Daya Tarik Makam Keramat Solear, Kabupaten Tangerang, dalam Meningkatkan Minat Kunjung Wisatawan - Allysa Syifa Syahirah; Rustini Rustini (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2023)
This study was based on initial observation on the Makam Keramat Solear indicated to have problems, namely, the lack of promotion of tourism and the underdevelopment of tourism destination. This causes the number of tourist visits has not increased. The purpose of this study was to analyze Makam Keramat Solear by using SWOT analysis, in order to determine the appropriate development strategy. This study used descriptive qualitative method. The results showed that the tourism destination of the Makam Keramat Solear was in quadrant IV. SWOT Analysis of Quadrant IV was a survival strategy, namely W-T (Weakness-Threat) Strategy, which aimed to survive by minimizing weaknesses and avoiding threats. Therefore, the strategy can be applied in developing the destination of the Sacred Tomb of Solear was a. creating promotion on various social media to compete with competitors' destinations; b. improving tourism infrastructures; c. eliminating the extortion activities so that tourists feel comfortable when visiting.